1997
DOI: 10.1007/bf01709592
|View full text |Cite
|
Sign up to set email alerts
|

Significance of indeterminate reactivity to human T-Cell lymphotropic virus in Western blot analysis of individuals at risk

Abstract: Current tests to confirm human T-cell lymphotropic virus (HTLV) infection in individuals at risk of retroviral infection commonly yield indeterminate results. To assess the significance of HTLV-seroindeterminate reactivities in a high-risk population, 16 at-risk individuals who had this serologic pattern by Western blot were studied using a polymerase chain reaction (PCR) assay. Human T-cell lymphotropic virus type II infection was confirmed by the presence of virus-specific nucleic acid in four patients. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…27 28 We found three HTLV-II infected women who had an indeterminate pattern on western blot. All three were Spanish natives, IDUs, and coinfected with HIV-1.…”
Section: Discussionmentioning
confidence: 86%
“…27 28 We found three HTLV-II infected women who had an indeterminate pattern on western blot. All three were Spanish natives, IDUs, and coinfected with HIV-1.…”
Section: Discussionmentioning
confidence: 86%
“…This approach is often accompanied by a high proportion of indeterminate WB results when low-risk populations, such as blood donors (1,10), are tested, although subsequent PCR analyses discharge the presence of HTLV-1/2 infection in almost all cases. In contrast, in high-risk populations, such as intravenous drug users (IDU), indeterminate HTLV WB patterns or even nonreactive EIA results may be seen in persons with true HTLV-2 infection (6,11). Since IDU are often coinfected with human immunodeficiency virus type 1 (HIV-1), it has been suggested that immunosuppression could explain the inability to mount and/or maintain an appropriate level of HTLV-2 antibodies, particularly in advanced stages of HIV disease (6).…”
mentioning
confidence: 99%
“…In contrast, in high-risk populations, such as intravenous drug users (IDU), indeterminate HTLV WB patterns or even nonreactive EIA results may be seen in persons with true HTLV-2 infection (6,11). Since IDU are often coinfected with human immunodeficiency virus type 1 (HIV-1), it has been suggested that immunosuppression could explain the inability to mount and/or maintain an appropriate level of HTLV-2 antibodies, particularly in advanced stages of HIV disease (6). A similar poor antibody response has been described for hepatitis C virus in HIV-positive individuals, causing "occult" infections (2).…”
mentioning
confidence: 99%
“…In general, indeterminate WB findings do not represent current HTLV infection 33 , but in high-risk populations or in endemic areas, an indeterminate WB result may represent a case at the seroconversion stage 20,34 . By using real-time PCR in the present study, we found nine samples that were EIA-positive and WB-indeterminate, and two of them (22.2%) were positive for HTLV-1.…”
Section: Referencesmentioning
confidence: 99%